Species richness and density of seabirds in Isla del Coco bays, Costa Rica, related to the occurrence of breeding colonies - Fourriére, Manon (2016)
Isla del Coco is one of the five oceanic islands situated on the eastern tropical Pacific Ocean and represents an important nesting and roosting site for seabirds. Despite several factors that can potentially impact its seabird fauna, knowledge about species density and distribution as well as of the size of its breeding colony is limited, currently consisting of bird checklists only. The objective of this study is to compare seabird species richness and density at four bays at Isla del Coco as a function of proximity to breeding colonies. In terms of richness, no pattern was identified. However, we found that the two sites situated near main breeding colonies had higher seabird densities (> 5 individuals ha-1) than the two sites without major breeding colonies. The difference in the densities could be explained by food availability and the presence of nesting habitat. It is possible that the seabirds are foraging near the colonies rather than venturing into long offshore trips.